Welfare and Labor Earnings: An Evaluation of the Financial Gains to Work - Marc Gurgand; David N. Margolis (Institute for the Study of Labor (IZA), 2002)
In this paper, we estimate the difference in long-run after-tax and transfer income from employment and from non-employment available in January 1998 to families in France that received the Guaranteed Minimum Income (RMI) in December 1996. Based on estimated wages we compute potential increases in disposable income (without accounting for opportunity costs such as child care or transportation). The observed wages received by welfare recipients are very low because of a high probability of part-time work, including for men. Based on the wage distribution, and supposing that the adult in the household with the highest potential earnings is the one employed, we find that 74% of welfare households would have an increase in disposable income if they were to be employed, relative to their disposable income in the absence of employment, and that the median gain would be around 198 euros per month. Very low gains are frequent however. In addition, single mothers are the group for which the fewest number of households (43%) would gain from employment. The share of households that would have in increase in income grows to 96% when we focus exclusively on couples and consider both members working. As the wage distribution used is very atypical, we build an upper bound estimate, using a representative survey of the working population in 1998. This is equivalent to assuming that RMI beneficiaries do not differ from the rest of the population in terms of their unobserved heterogeneity. The share of households that have an increase in disposable income from working goes from 74% to 89%, with the shares for single mothers still the lowest.
Keywords: C34; J31; I38; 330; Welfare; labor earnings; transfers; tax system; Erwerbstätigkeit; Verfügbares Einkommen; Haushaltseinkommen; Sozialtransfer; Sozialhilfeempfänger; Schätzung; Frankreich